ANALISIS PENGARUH BI RATE, SUKUK, DAN LIKUIDITAS TERHADAP PERMINTAAN SURAT UTANG NEGARA (SUN) DI INDONESIA - Rapianto, Alwi; Widayatsari, Any; Aulia, Ando Fahda (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The objective of this research is to example and analyze the effect of BI Rate, liquidity, and sukuk to on government bonds (SUN) in Indonesia from Year 2010-2016. This study used quarterly data sourced from the Directorate General of Debt Management, Ministry of Finance of the Republic of Indonesia, and Indonesia Financial Statistics Indonesia (SEKI), from Bank Indonesia (BI). This study used method of quantitative analysis using econometrics model. The results showed that partially, interest rate significantly affec positively on demand of government securities amounted to 0.001%. Sukuk significantly affected positively to the demand of government securities by 0.000% and liquidity has no significant effect on demand of government securities by 0.473%.